Use of a Fuzzy Decision-making Approach in an Analysis of the Vulnerability of Street Networks for Disaster Management - Zhang, Zhe; Virrantaus, Kirsi (Nordic Journal of Surveying and Real Estate Research, 2017)
Disaster management with respect to urban structures has received more attention in recent years. In disaster management, the most vulnerable structures in a modern society are the critical networks, such as transportation networks. The vulnerability analysis of spatial networks should not depend only on the topological structure; some non-topological attributes, such as population information, should also be considered. In a rescue operation, decision-making problems are very often uncertain or vague because of the lack of information. Therefore, the classi cation of a high or low-risk area on the basis of spatial information should not have crisp boundaries and it would be more reasonable to use a fuzzy approach. In this paper, population information and a betweenness centrality measure of the road network were used as the evaluation criteria, and a fuzzy multiple-attribute decision-making (MADM) approach was used to support a vulnerability analysis of the road network of Finland for disaster management. In order to validate the model, results were compared with original population information and a betweenness attribute map. The validation results showed the hotspots in a fuzzy MADM vulnerability map have a similar pattern to an original input attributes map and the number of hotspots were reduced to a reasonable scale in order to improve rescue e ciency.